2016
DOI: 10.2298/tsci151110220m
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and heat effects on polyethylene behaviour in the presence of imperfections

Abstract: This paper highlights the changes of polyethylene behaviour during various loading rates as well as the influence of test temperature on the material characteristics. Passive infrared thermography method and a high speed infrared camera were used to observe the temperature changes of the sample surface during the tests. The experimental program was carried out on samples taken from PE80 polyethylene gas pipes with simulated imperfections with bilateral V-notch, U-notch, and central hole. Samples have been tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This means that it takes a lot of energy to manipulate the HDPE material's temperature and initiate heat transfer over the thickness of the object. Regardless, a number of studies have demonstrated the effectiveness of IRT for polyethylene components, such as pipes [23][24][25], pipe joints [26][27][28], and composites [29]. To accommodate the low thermal diffusivity, six 500-watt halogen lamps with a total power of 3000 watts at a distance of 0.4 m were used to heat up the object for three minutes.…”
Section: Infrared Thermography (Irt)mentioning
confidence: 99%
“…This means that it takes a lot of energy to manipulate the HDPE material's temperature and initiate heat transfer over the thickness of the object. Regardless, a number of studies have demonstrated the effectiveness of IRT for polyethylene components, such as pipes [23][24][25], pipe joints [26][27][28], and composites [29]. To accommodate the low thermal diffusivity, six 500-watt halogen lamps with a total power of 3000 watts at a distance of 0.4 m were used to heat up the object for three minutes.…”
Section: Infrared Thermography (Irt)mentioning
confidence: 99%
“…For the purpose of measuring the temperature field, the infrared thermography method was used. This method has numerous applications, one of which is the quality assessment of high-density polyethilene (HDPE) pipes [3,7]. Infrared thermography involves the use of special thermographic cameras which detect radiation within the infrared spectrum, emitted by the specimen, and based on its levels, determine the temperature distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Polyethylene has found its application in the manufacturing of pipe systems, primarily for the transport of water and gas, wherein it has been used for over 40 years [1][2][3]. The main advantages over other materials used for pipelines include good weldability, corrosion resistance, and light weight [4].…”
Section: Introductionmentioning
confidence: 99%